Characteristics related to early secondary amenorrhoea and pregnancy among women diagnosed with systemic lupus erythematosus: an analysis using the GOAL study. (22nd September 2016) - Knight, Jessica H; Howards, Penelope P; Spencer, Jessica B; Tsagaris, Katina C; Lim, Sam S
Abstract : Objective: Systemic lupus erythematosus (SLE) disproportionately affects women and often develops during their reproductive years. Research suggests that some women who receive cyclophosphamide as treatment for SLE experience earlier decline in menstrual function, but reproductive health among women with SLE who have not taken this drug is less well understood. This study aims to better understand the relation between SLE and reproduction by assessing early secondary amenorrhoea and pregnancy in women treated with and without cyclophosphamide from a population-based cohort with large numbers of African-Americans. Methods: Female patients with SLE, ages 20–40 at time of diagnosis, who were 40 years or older at the time of the survey were included in this analysis (N=147). Participants in the Georgians Organized Against Lupus (GOAL) study were asked about their reproductive histories including early secondary amenorrhoea, defined as loss of menstruation before age 40. Results: Women who were cyclophosphamide naïve had an increased prevalence of early secondary amenorrhoea compared with population estimates, 13–17% compared with 1–5%. Factors associated with early secondary amenorrhoea in women not treated with cyclophosphamide were marital status and receipt of a kidney transplant. Treatment with cyclophosphamide doubled the prevalence after adjustment for patient characteristics. Over 88% of women reported being pregnant at least once, and about 83% of these had a child, but the majority of pregnancies occurred before diagnosis. Conclusions: SLE diagnosed in early adulthood may affect women's reproductive health even if they are not treated with cyclophosphamide. Better understanding of other factors related to reproductive health in this population will improve clinicians' and patients' abilities to make treatment and family planning decisions.